Book Review: Understanding American Hegemony - Zanuwar Hakim Atmantika (Universitas Gadjah Mada, 2023)
American hegemony refers to the dominant political, economic, and military position of the United States in the world since the end of World War II. The influence of American culture has become increasingly widespread in all aspects of life and has attracted the attention of academics, including American Studies scholars. The book entitled Understanding American Hegemony written by Kasiyarno is a work that explains American hegemony from the perspective of American Studies. The theoretical framework of this book departs from the Interdisciplinary approach, namely US hegemony from the perspective of culture (cultural hegemony), history and political science (international relations), economics, military, and regional (regionalism). Understanding American Hegemony is a book that emphasizes the study of how the U.S. experience grows and develops abroad and the reaction of the world or world community toward U.S. policies in disseminating its cultural values abroad. Besides, this book is expected to enrich American studies not only in its regional scopes but also in the direction of the study.